EFEKTIVITAS PENGGUNAAN APLIKASI E-SAMBAT DALAM MENINGKATKAN KUALITAS PELAYANAN PENGADUAN MASYARAKAT - Fauziya, Roudhotul; Said, Mohammad Mas’ud; Hayat, Hayat (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Problems/Background (GAP): The author focuses on problems where there is still a high level of complaints that have not received a good response, and it is seen that not many people use the application or the application is not widely known. This shows that the e-connection application has not been effective. In order to realize a good complaint facility in meeting the needs of the community in obtaining quality public services. So, the e-connection application must be improved and further improved. Purpose: The purpose of this study is to identify the effectiveness of using the E-Sambat application in improving the quality of public complaint services, supporting and inhibiting factors in the use of the E-Sambat application. Methods: This research uses a descriptive qualitative method with an inductive approach and an analysis of effectiveness theory according to Gibson (2011: 32) and measures service quality using the theory of Zeithmlin et al. quoted from (Hiplunudin, 2017: 112). Data collection techniques using observation, interviews, and documentation. Results/Findings: The main obstacle faced by the E-Sambat application is the low number of users which shows that this application has not been widely used by the people of Pasuruan City. Conclusion: The results of the study show that the e-Sambat application is very effective in improving the quality of public complaint services in Pasuruan City. The quality of the e-Sambat complaint service by the Municipal Government of Pasuruan is of sufficient quality. The e-Sambat public service by the Pasuruan City Government really has a positive long-term program and impact based on the results of the input of complaint reports that have been submitted by the people of Pasuruan City.